FIRM RESILIENCE RESEARCH DEVELOPMENT: A BIBLIOMETRIC ANALYSIS WITH VOSVIEWER - Metta Padmalia (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research examines the development of research on the topic of firm resilience which is currently very relevant to the conditions of the Covid-19 pandemic using bibliometric analysis with the support of the VOSviewer application. This study aims to find out: (1) the development of research on firm resilience published in international journals listed on the Scopus database from 1991-2021; (2) publication of international journals on corporate resilience; and (3) a map of the development of international research publications in the field of keyword-based firm resilience. Data collection was carried out through a search through the Scopus website with the keyword